2018
DOI: 10.1155/2018/1467595
|View full text |Cite
|
Sign up to set email alerts
|

Health Related Quality of Life of Cancer Patients in Ethiopia

Abstract: Background Neoplasm, AKA cancer (Ca), is associated with major morbidity and mortality. Aim Measurement of health related quality of life (HRQoL) of Ca patients is uncommon in Ethiopia. The present study determined the HRQoL and its determinants among people living with Ca in north Ethiopia. Methods A prospective hospital based study was conducted from 1 January 2017 to 30 August 2017 on Ca patients attending cancer treatment center of University of Gondar Teaching Hospital. The European Organization for Resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
62
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(80 citation statements)
references
References 24 publications
11
62
4
1
Order By: Relevance
“…The most pronounced differences were found for financial difficulties (d = 0.74). Two other studies with Ethiopian cancer patients [17,29] also reported high mean scores in these scales (64.8 and 69.9, respectively), similar to the mean of our Ethiopian study (67.1) and markedly higher than the mean score obtained in Germany (37.8). This difference illustrates that due to the lack of a health insurance system, the financial burden of cancer patients is considerable and this non-clinical factor is relevant for the QoL of patients in developing countries.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The most pronounced differences were found for financial difficulties (d = 0.74). Two other studies with Ethiopian cancer patients [17,29] also reported high mean scores in these scales (64.8 and 69.9, respectively), similar to the mean of our Ethiopian study (67.1) and markedly higher than the mean score obtained in Germany (37.8). This difference illustrates that due to the lack of a health insurance system, the financial burden of cancer patients is considerable and this non-clinical factor is relevant for the QoL of patients in developing countries.…”
Section: Discussionsupporting
confidence: 88%
“…Ethiopia ranks 173rd of the 183 countries in the Human Development Index [14]. Several studies have already been performed using the EORTC QLQ-C30 in Ethiopia [15][16][17][18][19]. All these five studies (with one exception) were performed at Tikur Anbessa Referral Hospital in Addis Ababa, the only oncology referral and radiotherapy center of the whole country.…”
Section: Introductionmentioning
confidence: 99%
“…23 However, this finding is higher than findings of some studies conducted in Malaysia (68.4%), Panama (65.3%), and Ethiopia (68% and 45.5%). 19,20,[23][24][25] The most probable reasons for the variation of results could be the level of service, the duration and stage of breast cancer at which patients seek care. In this study, most dominating management of breast cancer is chemotherapy (89.2%) which is consistent with the results of study conducted in Northern Ethiopia (96%).…”
Section: Discussionmentioning
confidence: 99%
“…31,32 However, it is inconsistent with studies conducted in different countries. 19,25,26,28,[34][35][36][37] The level of quality of care might vary among care providers and even among institutions where the care was provided. For instance, a study conducted in northern Ethiopia proved that there was no radiotherapy in its area during the study.…”
Section: Discussionmentioning
confidence: 99%
“…4 The burden of cancer overlaps with infectious diseases, such as HIV/ AIDS, tuberculosis, hepatitis virus, and human papillomavirus in low-and middle-income countries. 5 Studies indicate that approximately 150 cases per 100,000 cases attributed to cancer and 800 per 100,000 non-communicable diseases in Ethiopia, 6 and cancer accounted for about 5.8% of the total mortality in the country. 7 It is also the second leading causes of death from non-communicable diseases next to cardiovascular disorders.…”
Section: Introductionmentioning
confidence: 99%